Solvent exposure and cognitive ability at age 67: a follow-up study of the 1947 Scottish Mental Survey. Issue 6 (11th November 2009) - Dick, Finlay D; Bourne, Victoria J; Semple, Sean E; Fox, Helen C; Miller, Brian G; Deary, Ian J; Whalley, Lawrence J
Abstract : Objectives: Organic solvent exposure may be associated with cognitive impairment in later life although the evidence for this association is inconsistent. This study sought to examine the association between organic solvent exposure and cognitive function in later life. Methods: A prospective longitudinal study set in Aberdeen, Scotland examined 336 men and women born in 1936 who participated in the 1947 Scottish Mental Survey. Cognitive function at age 67 years was measured using the Trail Making Test B (TMT B), the Digit Symbol (DS) test, and the Auditory Verbal Learning Test (AVLT). Occupational hygienists reviewed occupational histories, blind to cognitive function, and estimated lifetime solvent exposures. Multiple regression analyses were employed to explore the association between solvent exposure and cognitive performance after adjustment for confounders. Results: After adjusting for childhood IQ, smoking, alcohol and sex, the solvent exposed group took on average almost 10 s longer than the unexposed group to complete the TMT B, a highly significant difference. For the DS test, after adjusting for childhood IQ, smoking and gender, the exposed group scored on average two points lower than the unexposed group, which was again highly significant. There was no evidence of an effect for cumulative solvent exposure on the TMT B or DS test. For the AVLT there were no significant differences associated with exposure. Conclusions: This study of subjects with generally low exposures, found no clear evidence of an association between solvent exposure and cognitive function.